2003
DOI: 10.1021/np030139y
|View full text |Cite
|
Sign up to set email alerts
|

ent-Kaurane Diterpenoids from Croton tonkinensis Inhibit LPS-Induced NF-κB Activation and NO Production

Abstract: Four ent-kaurane diterpenoids including two known, ent-7alpha,14beta-dihydroxykaur-16-en-15-one (1) and ent-18-acetoxy-7alpha-hydroxykaur-16-en-5-one (2), and two new, ent-1beta-acetoxy-7alpha,14beta-dihydroxykaur-16-en-15-one (3) and ent-18-acetoxy-7alpha,14beta-dihydroxykaur-16-en-15-one (4), were isolated from the leaves of Croton tonkinensis in a search for inhibitors of NF-kappaB activation and nitric oxide production. These ent-kauranoids inhibited LPS-induced NF-kappaB activation in murine macrophage RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
50
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 12 publications
0
50
0
3
Order By: Relevance
“…Four ent-akurane diterpenoids 32-35 84 of Croton tonkinensis leaves and five ent-akurane diterpenoids 36-40 85 ( Fig. 4) of Isodon excisus aerial parts strongly inhibited the NF-kB activation and NO production in LPS-stimulated RAW 264.7 cells.…”
Section: Terpenoidsmentioning
confidence: 95%
See 1 more Smart Citation
“…Four ent-akurane diterpenoids 32-35 84 of Croton tonkinensis leaves and five ent-akurane diterpenoids 36-40 85 ( Fig. 4) of Isodon excisus aerial parts strongly inhibited the NF-kB activation and NO production in LPS-stimulated RAW 264.7 cells.…”
Section: Terpenoidsmentioning
confidence: 95%
“…This functional group can react with biological nucleophiles, especially the sulfhydryl group of the cysteine residue in the DNA-binding domain of the NF-kB subunit. 84,85 Taraxasteryl acetate (41) isolated from Pluchea sagittalis showed activity against H 2 O 2 -, phorbol 12-myristate 13-acetate (PMA)-and fMLP-induced ROS, sodium nitroprusside-induced reactive nitrogen species, and heat shock protein72 production in human neutrophils; and exhibited more potent topical anti-inflammatory activity than indomethacin in AA-, croton oil-and PMAinduced mice ear edema. 86 Agnuside (42), an iridoid glycoside, isolated from Vitex peduncularis showed a preferential inhibition of COX-2 greater than aspirin (IC 50 0.058 mg/mL), a nonselective COX-2 inhibitor.…”
Section: Terpenoidsmentioning
confidence: 99%
“…4,7) Among them, the ent-kaurane diterpenoids have cytotoxic and proapoptotic activities, 8) inhibit lipopolysaccharide-induced nuclear factor kappa B activation, 9) reduce inflammation, 10) inhibit silent information regulator two ortholog 1 (SIRT1), 11) and stimulate osteoblast differentiation. 12) AMP-activated protein kinase (AMPK) is a cellular energy status sensor found in all eukaryotes, which is activated under conditions of low intracellular ATP following stressors such as nutrient deprivation and hypoxia.…”
mentioning
confidence: 99%
“…[13][14][15][16] In addition, ent-kaurane diterpenes isolated from Rabdosia rubescens or Croton tonkinensis, showed anti-inflammatory activities in primary cultured rat microglia or RAW264.7 macrophages. 17,18) Moreover, Park et al found that siegeskaurolic acid, an ent-kaurane diterpene isolated from S. pubescens, significantly inhibited lipopolysaccharide (LPS)-induced inflammatory responses in RAW264.7 cells through down-regulation of the NF-κB binding activity. 19) Kirenol isolated from Herba Siegesbeckiae also reduces proinflammatory cytokines secretion, increase anti-inflammatory cytokines production of CII-specific lymphocytes from CIA rats, and exerts a potent anti-arthritic effect in collageninduced arthritis by modifying the balance of T cells.…”
mentioning
confidence: 99%